Additional value of B-type natriuretic peptide on discrimination of patients at risk for mortality after a non-ST-segment elevation acute coronary syndrome. Issue 2 (1st June 2014) - García-Alvarez, Ana; Regueiro, Ander; Hernández, Jaime; Kasa, Gizem; Sitges, Marta; Bosch, Xavier; Heras, Magda
Abstract: Background: Few studies have addressed the additional value of B-type natriuretic peptide (BNP) on risk stratification in non-ST-elevation acute coronary syndrome (NSTE-ACS). We aimed to evaluate whether BNP levels provide additional improvement on discrimination and reclassification of patients at risk of mortality during admission and follow up after a NSTE-ACS. Methods: BNP levels were measured 24–96 hours post admission in 600 patients with a NSTE-ACS. The incremental predictive value of including BNP into the multivariate models with the highest predictive accuracy for mortality during admission (logistic regression) and follow up (Cox regression) and over the Thrombolysis in Myocardial Infarction (TIMI) and Global Registry of Acute Coronary Events (GRACE) risk scores was assessed using calibration, discrimination (area under the ROC curve (AUC) and Harrell's C statistic), and reclassification measures (net reclassification improvement (NRI) and index discrimination improvement (IDI)). Results: A total of 19 (3.2%) patients died during admission and 29 (4.1%) during follow up (median 13.4 months). BNP was independently associated with mortality during admission (OR 3.56, 95% CI 1.75–7.23) and improved discrimination (AUC 0.95 vs. 0.92, p =0.01) and reclassification (NRI 72% and IDI 8%, p <0.05 for both). Similarly, BNP was an independent predictor of mortality during follow up (HR 2.46, 95% CI 1.94–3.12) and provided additional discriminative value (Harrell's C 0.86 vs. 0.84, p =0.04). Similarly, BNP demonstrated additional value above the TIMI and GRACE scores. Conclusions: Determination of BNP 24–96 hours after a NSTE-ACS improved discrimination of patients at risk for mortality during admission and follow up.